Leadership for Successful School Reform - Salihu, Muftahu Jibirin (School of Social Sciences, 2015)
In this research paper, the concept of teacher leadership will be discussed in full detail in the context of “leadership for successful school reform”. This research paper will practically discuss leadership as a concept that serves as the main key for the attainment of a successful and effective school reform, and the reasons for this claim will be thoroughly discussed in this paper. In addition, this paper will be presenting a developed coherent picture of the workplace challenges being encountered by the researcher in the present college where he is teaching. Some of the major challenges in the educational workplace that is experienced by the researcher of this paper will be thoroughly discussed in order to lead the discussion on how leadership may be able to effectively solve such issues or challenges being encountered by the teachers in the college where they serve. In addition, this research paper will also be emphasizing on the role of “project facilitator’s” as parallel leaders.